The Role of CD40, CD86, and Glutathione S-Transferase Omega 1 in the Pathogenesis of Chronic Obstructive Pulmonary Disease - Desheng Sun; Rong Lin; Yao Ouyang (Canadian Respiratory Journal)
Objective. The aim of the study was to explore the relevance of CD40, CD86, and GSTO1 with the pathogenesis of COPD. Methods. Patients with acute exacerbation of COPD were contrasted with the healthy and nonsmoking ones and smoking but without COPD ones. The changes of CD40, CD86, and GSTO1 in the peripheral blood, collected from different groups, were detected by flow cytometry and western blotting, respectively. Results. Compared with the nonsmoking group and smoking but without the COPD group, the expression of CD40 and CD86 of the patients with COPD increased significantly, but the expression of GSTO1 decreased. CD40 and CD86 were negatively correlated with FEV1%, while GSTO1 was positively correlated with FEV1% and negatively correlated with CD40 and CD86. Conclusion. CD40, CD86, and GSTO1 may play a role in the pathogenesis of COPD, and they are related to the severity of COPD and the degree of changes in the lung function.